Preconception Care in Women with Diabetes (BIRDEM Medical Journal, 2017)
For women of reproductive age preconception care is a crucial component. The main goal of preconception care is to provide screening, detection and management of medical conditions that might affect future pregnancies. Preconception care is defined as a care that aim to identify and modify risks during pregnancy and improves pregnancy outcome through prevention and management. It is not only a single visit to a health-care provider but it will include full facilities of preventive and primary care services for women before a pregnancy or between pregnancies Improved preconception care is also a mandatory component for women with diabetes. Not only for women but men also need improvement of the knowledge, attitudes and behaviors related to reproductive health to maintain an ideal preconception health. For a good pregnancy out come proper preconception counseling, good glycemic control, screening and management of diabetic complications is essential.Birdem Med J 2017; 7(2): 164-167